BEYOND THE SCREEN: THE RETCONNING OF BLACK CHARACTERS IN POPULAR CULTURE MOVIES THROUGH THE LENS OF BLACKWASHING - Lu'lu'a, Lu'lu'a; Asysyamil, Muhammad Fikri; Zain, Ahsan; Hanif, Dzulfikar; Ros, Gerry; Pratama, Rizky Viko (CrossOver, 2024)
The portrayal and adaptation of characters in movies often reflect societal norms and values, with "blackwashing" emerging as a significant phenomenon. Blackwashing refers to casting black actors in roles traditionally portrayed by white characters, often as part of efforts to promote representation and address historical inequalities. This study explores the types of retroactive continuity (retcon) found in black characters within popular culture films through the perspective of blackwashing. The research employs Hutcheon’s (2013) adaptation theory, which conceptualizes adaptation as creative reinterpretation rather than mere replication, alongside Friedenthal’s (2017) retcon framework and Genette’s (1997) qualitative transformation theory for supplementary analysis. Using a qualitative approach, the study applies the documentation method for data collection and Spradley’s (2016) analysis technique. Seven adapted films (hypertexts) are compared to their original works (hypotexts), revealing three distinct types of retcon: reinterpretation, reinscription, and revision. These findings demonstrate how adaptation practices not only reshape narratives but also challenge traditional representations to align with evolving social values. The findings highlight how adaptation practices reshape narratives to address historical inequalities and enrich representation in media. This research contributes to the understanding of blackwashing as a tool for inclusivity and social progress in film adaptation. Future studies are recommended to explore blackwashing across diverse cultural contexts and genres to deepen insights into its impact on global representation and audience reception.